PENGEMBANGAN APLIKASI ANDROID SEBAGAI MEDIA PEMBELAJARAN BERBASIS ANDROID PADA KOMPETENSI DASAR TROUBLESHOOTING MIKROKONTROLER DI SMKN 1 DRIYOREJO - Azmi, Subhan; Widodo, Arif; Basuki, Ismet; Sumbawati, Meini Sondang (Jurnal Pendidikan Teknik Elektro, 2021)
Many studies discuss android-based learning media, but there is no research that specifically discusses troubleshooting on the Arduino IDE. This study aims to create an android-based learning media product by taking the basic competence of troubleshooting input output in the subjects of Microprocessor and Microcontroller Programming Engineering (TPMM). With the learning media called ArduinoID, it is hoped that students can understand more about troubleshooting Arduino IDE, especially on writing errors. This research is a development research that uses the ADDIE model. The subjects of this study were 66 students of class X TEI SMKN 1 Driyorejo. This research design uses a one group pretest-posttest design to compare the results before and after treatment. ArduinoID learning media development utilizes an android developer site called Kodular. The results showed that the ArduinoID learning media validation results from 2 lecturers and 2 teachers got a validation value of 89.10% with very good criteria. From the students' responses to the ArduinoID learning media, they got a response of 84.70% with the criteria of strongly agreeing. Then, in testing the effectiveness of learning media using IBM SPSS Statistics 23 Software, ArduinoID obtained a significance value (2-tailed) of 0.000 < 0.05. So it can be concluded that there is a significant difference (increase) between learning outcomes in pre-test and post-test data. From the various analyzes that have been carried out, it can be concluded that the ArduinoID application is feasible as a learning medium in class X TEI students at SMKN 1 Driyorejo.